Flagship 2: Economywide factors affecting agricultural growth and rural transformation - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Policy options to promote inclusive rural growth and transformation ● Agriculture as a source of jobs as well as food ● Public investments for vibrant rural areas ● The political economy of agricultural policy reforms